Disruption of the Phagosomal Membrane and Egress of Legionella pneumophila into the Cytoplasm during the Last Stages of Intracellular Infection of Macrophages and Acanthamoeba polyphaga - Molmeret, Maëlle (American Society for Microbiology, 2004)
Although the early stages of intracellular infection by Legionella pneumophila are well established at the ultrastructural level, a detailed ultrastructural analysis of late stages of intracellular replication has never been done. Here we show that the membrane of the L. pneumophila-containing phagosome (LCP) is intact for up to 8 h postinfection of macrophages and Acanthamoeba polyphaga. At 12 h, 71 and 74% of the LCPs are disrupted within macrophages and A. polyphaga, respectively, while the plasma membrane remains intact. At 18 and 24 h postinfection, cytoplasmic elements such as mitochondria, lysosomes, vesicles, and amorphous material are dispersed among the bacteria and these bacteria are considered cytoplasmic. At 18 h, 77% of infected macrophages and 32% of infected A. polyphaga amoebae harbor cytoplasmic bacteria. At 24 h, 99 and 78% of infected macrophages and amoebae, respectively, contain cytoplasmic bacteria. On the basis of lysosomal acid phosphatase staining of infected macrophages and A. polyphaga, the lysosomal enzyme is present among the bacteria when host vesicles are dispersed among bacteria. Our data indicate that bacterial replication proceeds despite physical disruption of the phagosomal membrane. We also show that an lspG mutant that is defective in the type II secretion system and therefore does not secrete the hydrolytic enzymes metalloprotease, p-nitrophenol phosphorylcholine hydrolase, lipase, phospholipase A, and lysophospholipase A is as efficient as the wild-type strain in disruption of the LCP. Therefore, L. pneumophila disrupts the phagosomal membrane and becomes cytoplasmic at the last stages of infection in both macrophages and A. polyphaga. Lysosomal elements, mitochondria, cytoplasmic vesicles, and amorphous material are all dispersed among the bacteria, after phagosomal disruption, within both human macrophages and A. polyphaga. The disruption of the LCP is independent of the hydrolytic enzymes exported by the type II secretion system.